William James and the Deepest South - Alexandre Mendes (Transatlantica)
This paper examines the impact on William James’s philosophical initiation of his trip to Brazil, in particular the Thayer Expedition (1865-1866), led by the Swiss-American scientist Louis Agassiz. My approach seeks to explore a “Southern transatlantic axis” in James’s thinking, which, I argue, has played a key role in the composition of his pluralistic point of view.